Application of Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanoscale enzyme in detection of fluoroquinolone antibiotics

CN122983004APending Publication Date: 2026-10-27LIAONING UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611264598.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

虽然这些方法具有较高的灵敏度和准确度,但仪器价格昂贵,操作步骤复杂,限制了它们的实际应用

Benefits of technology

[0016]本发明的有益效果是:本发明制备的一种Zr/Cu-UiO-66-NH2荧光-比色双功能纳米酶材料在铜的掺杂后,会在UiO-66-NH2的晶格中引入大量缺陷,引入缺陷后能有效增强材料的自荧光和过氧化物酶活性。此材料对于检测诺氟沙星有较低的检出限,本发明的检测方法方便快捷,有利于检测。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122983004A_ABST
    Figure CN122983004A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of detection, and particularly relates to application of Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanoscale enzyme in detection of fluoroquinolone antibiotics. Zirconium chloride, copper nitrate trihydrate and 2-amino terephthalic acid are dissolved in N,N-dimethylformamide, after ultrasonic treatment, glacial acetic acid is added, and then ultrasonic treatment is carried out, the mixed solution is poured into a polytetrafluoroethylene autoclave, reaction is carried out at 120 DEG C, and the obtained product is collected by centrifugation, vacuum dried at 60 DEG C, and the product Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanoscale enzyme is obtained. After doping of copper, the Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanoscale enzyme material prepared in the application can introduce a large number of defects in the crystal lattice of UiO-66-NH2, and after introduction of the defects, the self-fluorescence and peroxidase activity of the material can be effectively enhanced. The material has a low detection limit for detection of norfloxacin, and the detection method of the application is convenient and fast, and is conducive to detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of detection technology, specifically relating to the application of a Zr / Cu-UiO-66-NH2 fluorescence-colorimetric bifunctional nanozyme in the detection of fluoroquinolone antibiotics. Background Technology

[0002] Fluoroquinolone antibiotics (FQs) (such as enrofloxacin, ciprofloxacin, and norfloxacin) are a class of broad-spectrum synthetic antibacterial drugs with strong antibacterial activity against both Gram-negative and Gram-positive pathogens. In veterinary medicine, fluoroquinolone antibiotics are widely used in livestock and aquaculture to prevent and treat bacterial infections, ensuring animal health and maintaining economic productivity. However, excessive use of fluoroquinolones and thioglycolic acid antibiotics in livestock and aquaculture can lead to drug residues in animal-derived products, posing a significant risk to human health and the environmental ecosystem. Therefore, accurate detection of antibiotic residues in various environmental and food samples is crucial.

[0003] Various analytical techniques for the detection of fluorescence-quantitative ionization (FQs), such as high-performance liquid chromatography (HPLC), mass spectrometry, chemiluminescence analysis (CL), surface plasmon resonance (SPR), and capillary indicators, have been developed. While these methods offer high sensitivity and accuracy, the high cost of the instruments and the complexity of the procedures limit their practical application. Therefore, establishing a simple, rapid, and accurate FQs detection method based on fluorescence-colorimetry is of great significance. Dual-mode detection using both colorimetry and fluorescence not only enables efficient, rapid, and low-cost analysis but also provides self-validating dual-signal output, effectively eliminating interference and enhancing detection reliability.

[0004] MOF materials consist of metal nodes and organic ligands, and their structural tunability allows for precise modulation of enzyme-like activity by altering the metal type, ligand structure, or synthesis conditions. Currently reported MOF nanozymes can mimic the catalytic functions of various natural enzymes, such as peroxidases, oxidases, and phosphatases. In particular, UiO-66-NH2, as a stable zirconium-based MOF, is widely used as a research model for nanozymes due to its functionalizable amino groups and good biocompatibility. Based on a heterovalent copper doping strategy, a Zr / Cu-UiO-66-NH2 bimetallic MOF nanozyme was constructed. Utilizing its peroxide activity and intrinsic fluorescence properties, a fluorescence-colorimetric bifunctional nanozyme sensor for the detection of fluoroquinolone antibiotics was developed. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention synthesizes Zr / Cu-UiO-66-NH2 via a hydrothermal method. The doping of heterovalent Cu introduces numerous defects into the UiO-66-NH2 lattice, effectively enhancing the material's autofluorescence and peroxidase activity, and promoting the efficient catalysis of TMB oxidation by H2O2. In the presence of fluorescence ions (FQs), the fluorescence and peroxidase activity of Zr / Cu-UiO-66-NH2 are significantly enhanced, thus establishing a fluorescence-colorimetric bifunctional method for detecting FQs.

[0006] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0007] Application of a Zr / Cu-UiO-66-NH2 fluorescence-colorimetric bifunctional nanozyme in the detection of fluoroquinolone antibiotics.

[0008] Furthermore, in the above applications, the detection methods are colorimetric detection and fluorescence detection.

[0009] Furthermore, in the above application, the colorimetric detection method is as follows: Under conditions of pH=3.5 and temperature of 40℃, take 50μL of a solution containing a fluoroquinolone antibiotic and add it to a final volume of 50μL to obtain a concentration of 0.25mg·mL. -1 The mixture was incubated in a Zr / Cu-UiO-66-NH2 suspension and 800 μL of buffer solution for 15 min. Then, 50 μL of 5 mM TMB solution and 50 μL of 15% H2O2 solution were added, and the mixture was incubated for another 20 min. The absorbance of the system was measured at a wavelength of 652 nm, and the colorimetric detection of fluoroquinolone antibiotics was performed based on the absorbance.

[0010] Furthermore, in the above application, the fluorescence detection method is as follows: Take 100 μL of Zr / Cu-UiO-66-NH2 suspension with a concentration of 2 mg / mL and place it in a container. Add 300 μL of a solution containing fluoroquinolone antibiotics. Add solvent to make the total volume of the mixed solution 4 mL. After mixing, collect the fluorescence emission spectrum and record the fluorescence intensity at 450 nm. The fluorescence detection of fluoroquinolone antibiotics is achieved based on the fluorescence intensity.

[0011] Furthermore, in any of the above applications, the fluoroquinolone antibiotic is norfloxacin.

[0012] Furthermore, in any of the above applications, the preparation method of the Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme includes the following steps: dissolving zirconium chloride, copper nitrate trihydrate, and 2-aminoterephthalic acid in DMF, sonicating them, adding glacial acetic acid, and sonicating them again; pouring the uniformly mixed solution into a polytetrafluoroethylene autoclave, heating the reaction, and cooling to room temperature; collecting the obtained product by centrifugation, washing it three times each with DMF and ethanol, and drying it under vacuum at 60°C to obtain the product Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme.

[0013] Furthermore, in the above-mentioned method for preparing the Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme, the molar ratio is zirconium chloride:copper nitrate trihydrate:2-aminoterephthalic acid = 0.4:0.6:1.

[0014] Furthermore, in the above-mentioned method for preparing Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozymes, the ultrasonic treatment time is 3 minutes.

[0015] Furthermore, in the above-mentioned method for preparing the Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme, the heating reaction conditions are: reacting at 120℃ for 24 h.

[0016] The beneficial effects of this invention are as follows: The Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme material prepared by this invention, after copper doping, introduces a large number of defects into the UiO-66-NH2 lattice. These defects effectively enhance the material's autofluorescence and peroxidase activity. This material has a low detection limit for norfloxacin, and the detection method of this invention is convenient and rapid, facilitating detection. Attached Figure Description

[0017] Figure 1 This is a SEM image of Zr / Cu-UiO-66-NH2.

[0018] Figure 2 This is the XRD pattern of Zr / Cu-UiO-66-NH2.

[0019] Figure 3 This is a comparison chart of enzyme activities between Zr / Cu-UiO-66-NH2 and UiO-66-NH2 materials.

[0020] Figure 4 This is a comparison of the fluorescence intensity of Zr / Cu-UiO-66-NH2 and UiO-66-NH2 materials.

[0021] Figure 5The diagram shows the optimized activity conditions of Zr / Cu-UiO-66-NH2 nanozymes. (A): Temperature, (B): pH.

[0022] Figure 6 This is a graph showing the optimized addition amount for fluorescence testing of Zr / Cu-UiO-66-NH2.

[0023] Figure 7 This is a linear relationship graph of colorimetric detection between Zr / Cu-UiO-66-NH2 and NOR.

[0024] Figure 8 The results are the colorimetric detection selectivity experiment (a) and the anti-interference experiment (b) of Zr / Cu-UiO-66-NH2 for detecting NOR.

[0025] Figure 9 This is a linear relationship graph of fluorescence detection between Zr / Cu-UiO-66-NH2 and NOR.

[0026] Figure 10 The results are the fluorescence detection selectivity experiment (a) and the anti-interference experiment (b) of Zr / Cu-UiO-66-NH2 for detecting NOR. Detailed Implementation

[0027] Example 1: Preparation of a Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme

[0028] (I) Preparation method

[0029] 1. Preparation of Zr / Cu-UiO-66-NH2

[0030] 93.2 mg zirconium chloride, 144.9 mg copper nitrate trihydrate, and 181 mg 2-aminoterephthalic acid were dissolved in 43.57 mL of N,N-dimethylformamide (DMF). After sonication for 3 min, 10 mL of glacial acetic acid was added, followed by another 3 min of sonication. The well-mixed solution was poured into a polytetrafluoroethylene autoclave and reacted at 120 °C for 24 h, then cooled to room temperature. The resulting product was collected by centrifugation, washed three times each with DMF and ethanol, and dried under vacuum at 60 °C to obtain the product Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme.

[0031] 2. Preparation of UiO-66-NH2

[0032] 233 mg of zirconium chloride and 181 mg of 2-aminoterephthalic acid were dissolved in 43.57 mL of N,N-dimethylformamide (DMF). After sonication for 3 min, 10 mL of glacial acetic acid was added, followed by sonication for another 3 min. The well-mixed solution was poured into a polytetrafluoroethylene autoclave and reacted at 120 °C for 24 h, then cooled to room temperature. The resulting product was collected by centrifugation, washed three times each with DMF and ethanol, and dried under vacuum at 60 °C to obtain product UiO-66-NH2.

[0033] (II) Testing

[0034] 1. The morphology of Zr / Cu-UiO-66-NH2 was studied and analyzed using SEM.

[0035] Figure 1 The image shows a scanning electron microscope (SEM) image of the prepared Zr / Cu-UiO-66-NH2, which has an octahedral structure.

[0036] 2. The crystal structure of Zr / Cu-UiO-66-NH2 was studied and analyzed using XRD.

[0037] Figure 2 This is the XRD pattern of the prepared Zr / Cu-UiO-66-NH2. In the XRD pattern, characteristic diffraction peaks corresponding to the simulated UiO-66-NH2 pattern were observed, confirming the successful synthesis of UiO-66-NH2. After Cu doping, these main diffraction peaks did not show significant shifts, indicating that the crystal structure framework of UiO-66-NH2 was preserved. Notably, the diffraction peak intensities of Zr / Cu-UiO-66-NH2 decreased, suggesting that heterovalent copper doping may lead to a slight decrease in the crystallinity of the material.

[0038] 3. Evaluation of peroxidase activity of Zr / Cu-UiO-66-NH2.

[0039] To verify the peroxidase activity of Zr / Cu-UiO-66-NH2, 50 μL of 5 mM TMB solution, 50 μL of 15% H2O2 solution, and 850 μL of acetate buffer were added to 50 μL of Zr / Cu-UiO-66-NH2 with a concentration of 1 mg / mL. The mixture was incubated at 40 °C for 20 min, and the UV absorbance at 652 nm was measured. Figure 3Only when TMB and H2O2 coexist does Zr / Cu-UiO-66-NH2 catalyze the oxidation of colorless TMB to blue oxTMB, with the absorbance center located at 652 nm, indicating that Zr / Cu-UiO-66-NH2 exhibits peroxidase catalytic activity. At 652 nm, the absorbance of the H2O2-TMB system is relatively low. In contrast, after the addition of Zr / Cu-UiO-66-NH2, a significant change in the solution's UV-Vis absorption peak characteristics was observed, indicating that Zr / Cu-UiO-66-NH2 possesses superior peroxidase activity and can catalyze the H2O2-induced oxidation of TMB.

[0040] 4. Evaluation of the fluorescence intensity of Zr / Cu-UiO-66-NH2.

[0041] To verify the fluorescence intensity of Zr / Cu-UiO-66-NH2, a Zr / Cu-UiO-66-NH2 suspension with a concentration of 1 mg / mL was used to measure its fluorescence intensity. Figure 4 In contrast, the Zr / Cu-UiO-66-NH2 suspension exhibited significant changes in fluorescence peak characteristics, demonstrating superior fluorescence.

[0042] 5. Optimization of peroxidase activity of Zr / Cu-UiO-66-NH2.

[0043] like Figure 5 , Figure 5 (B) describes the optimization of the buffer solution's pH. We added 50 μL of 5 mM TMB solution, 50 μL of 15% H2O2 solution, and 850 μL of acetate buffer solutions with different pH values ​​(3, 3.5, 4, 4.5, 5, 5.5, 6, 6.5) to 50 μL of 1 mg / mL Zr / Cu-UiO-66-NH2. After incubation at 40°C for 20 min, we measured the UV absorbance at 652 nm. We found that the absorbance was highest at pH 3.5, indicating that the peroxidase activity of Zr / Cu-UiO-66-NH2 was highest at this pH value. Therefore, the optimal pH is 3.5. Similarly, Figure 5 In (A), the temperature was optimized by changing only the incubation temperature. It was found that the absorbance was highest at 40℃, which proved that the peroxidase activity of Zr / Cu-UiO-66-NH2 was the highest at this temperature, and the optimal temperature was 40℃.

[0044] 6. Optimization of fluorescence experimental conditions for Zr / Cu-UiO-66-NH2.

[0045] like Figure 6 , Figure 6This study optimized the amount of Zr / Cu-UiO-66-NH2 material added for fluorescence detection. We prepared a Zr / Cu-UiO-66-NH2 suspension with a concentration of 2 mg / mL. Different volumes of Zr / Cu-UiO-66-NH2 suspension were added to a series of plastic test tubes, and different volumes of deionized water were added to the samples to ensure a total mixed solution of 4 mL. After mixing, the fluorescence emission spectra were recorded. Since the fluorescence intensity difference between 200 µL and 100 µL of Zr / Cu-UiO-66-NH2 suspension was small, we selected 100 µL as the optimal addition amount.

[0046] Example 2: Colorimetric detection of norfloxacin using Zr / Cu-UiO-66-NH2

[0047] (I) Effect of different concentrations of norfloxacin on absorbance

[0048] Use a concentration of 0.25 mg / mL -1 Norfloxacin was detected in a Zr / Cu-UiO-66-NH2 suspension at pH 3.5 and 40℃. 50 μL of norfloxacin solutions of different concentrations were added to 50 μL of Zr / Cu-UiO-66-NH2 suspension and 800 μL of buffer solution, incubated for 15 min, then 50 μL of TMB (5 mM) and 50 μL of H2O2 (15%) were added, and incubated for 20 min. The absorbance was measured at 652 nm. Figure 7 As the concentration of norfloxacin increases, the absorbance signal strengthens. Furthermore, there is a linear relationship between absorbance and concentration. The limit of detection (LOD) for NOR, calculated using the formula 3σ / k, is 0.135 μM.

[0049] (II) Selectivity and anti-interference test of norfloxacin detection using Zr / Cu-UiO-66-NH2

[0050] 1. Selectivity experiment for colorimetric detection of norfloxacin using Zr / Cu-UiO-66-NH2

[0051] Figure 8 (A) shows the selectivity experiment for the colorimetric detection of norfloxacin using Zr / Cu-UiO-66-NH2. We added 50 μL of TMB solution, 50 μL of H2O2 solution, and 50 μL of Zr / Cu-UiO-66-NH2 suspension to 800 μL of acetate buffer, followed by the addition of 50 μL of NOR solution or 5 mmol / L of [the solution used]. -1 Interfering substances (Na) + K + Ca 2+ NH4+ Cl - CO3 2- SO4 2- HPO4 2- H2PO4 - (TC, OTC), after mixing, react at 40℃ for 20 minutes, and the maximum absorbance of the reaction solution at 652 nm is measured using a UV-Vis absorption spectrometer. Figure 8 As shown in (A), most interfering substances are not significant, indicating good selectivity for norfloxacin.

[0052] 2. Anti-interference experiment of colorimetric detection of norfloxacin using Zr / Cu-UiO-66-NH2

[0053] Figure 8 (B) shows the anti-interference experiment of Zr / Cu-UiO-66-NH2 for the colorimetric detection of norfloxacin. We added 50 μL of TMB solution, 50 μL of H2O2 solution, 50 μL of Zr / Cu-UiO-66-NH2 suspension, 50 μL of NOR solution, and 50 μL of 5 mmol L to 750 μL of acetate buffer solution. -1 Interfering substances (Na) + K + Ca 2+ NH4 + Cl - CO3 2- SO4 2- HPO4 2- H2PO4 - (TC, OTC), after mixing, react at 40℃ for 20 minutes, and the maximum absorbance of the reaction solution at 652 nm is measured using a UV-Vis absorption spectrometer. Figure 8 As shown in (B), when the above substances are present in a reaction system containing Zr / Cu-UiO-66-NH2, TMB, and H2O2, the UV absorption intensity is approximately equal to that containing only NOR. The results indicate that this detection system has good anti-interference capability against NOR activity.

[0054] Example 3: Fluorescence detection of norfloxacin using Zr / Cu-UiO-66-NH2

[0055] (I) Effect of different concentrations of norfloxacin on fluorescence intensity

[0056] A Zr / Cu-UiO-66-NH2 suspension with a concentration of 2 mg / mL was used. 100 µL of freshly prepared Zr / Cu-UiO-66-NH2 suspension was added to a series of plastic test tubes. 300 μL of NOR aqueous solution of different concentrations was added to each sample to ensure a total mixed solution volume of 4 mL. The fluorescence emission spectra were recorded after mixing. Figure 9 As the concentration of norfloxacin increases, the fluorescence intensity signal strengthens. Furthermore, a linear relationship exists between fluorescence intensity and concentration. The limit of detection (LOD) for NOR, calculated using the formula 3σ / k, is 0.015 μM.

[0057] (II) Selectivity and anti-interference experiment of fluorescence detection of norfloxacin using Zr / Cu-UiO-66-NH2

[0058] 1. Selectivity experiment for fluorescence detection of norfloxacin using Zr / Cu-UiO-66-NH2

[0059] Figure 10 (A) shows the selectivity experiment for the fluorescence detection of norfloxacin using Zr / Cu-UiO-66-NH2. We prepared a Zr / Cu-UiO-66-NH2 suspension at a concentration of 2 mg / mL. 100 μL of the Zr / Cu-UiO-66-NH2 suspension was added to a series of plastic test tubes, and 3900 μL of NOR solution or 5 mmol / L of NOR solution was added to the sample, respectively. -1 Different interfering substances (Na) + K + Ca 2+ NH4 + Cl - CO3 2- SO4 2- HPO4 2- H2PO4 - (TC, OTC), to ensure the mixed solution is 4 mL, and record the fluorescence intensity at 450 nm after mixing. Figure 10 As shown in (A), most interfering substances are not significant, indicating good selectivity for norfloxacin.

[0060] 2. Anti-interference experiment of using Zr / Cu-UiO-66-NH2 to detect norfloxacin

[0061] Figure 10(B) shows the anti-interference experiment of Zr / Cu-UiO-66-NH2 against norfloxacin detection. We prepared a Zr / Cu-UiO-66-NH2 suspension with a concentration of 2 mg / mL. 100 μL of the Zr / Cu-UiO-66-NH2 suspension was added to a series of plastic test tubes, and 300 μL of NOR solution and 300 μL of different interfering substances (Na+, Na ... + K + Ca 2+ NH4 + Cl - CO3 2- SO4 2- HPO4 2- H2PO4 - (TC, OTC), add solvent to make the total volume of the mixed solution 4 mL, and record the fluorescence intensity at 450 nm in the fluorescence emission spectrum after mixing. Figure 10 As shown in (B), when the above-mentioned substance is present in a reaction system containing Zr / Cu-UiO-66-NH2, the fluorescence intensity is approximately equal to that containing only NOR. The results indicate that this detection system has good anti-interference capability against NOR activity.

[0062] Example 4: Evaluation of the detection effect of norfloxacin concentration in actual samples

[0063] During the testing process, lake water and honey were used as actual samples for norfloxacin analysis. Different concentrations of the analyte (0.1 μmol / L) were added to the samples. -1 1 μmol L -1 10 μmol L -1 The precision and accuracy of colorimetric and fluorescence methods were studied using spiking methods.

[0064] Table 1. Detection efficacy of colorimetric and fluorescence methods for norfloxacin concentration in real samples.

[0065]

[0066] As shown in Table 1, Zr / Cu-UiO-66-NH2 exhibits superior analytical performance for norfloxacin, with recoveries ranging from 87.50% to 100.34%. This indicates that the nanozyme sensor possesses high recovery and good precision, making it suitable for detecting trace amounts of norfloxacin in real-world samples.

Claims

1. Application of a Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme in the detection of fluoroquinolone antibiotics.

2. The application according to claim 1, characterized in that, The detection methods are colorimetric detection and fluorescence detection.

3. The application according to claim 2, characterized in that, The colorimetric detection method is as follows: Under conditions of pH=3.5 and temperature of 40℃, take 50μL of a solution containing fluoroquinolone antibiotics and add it to a final volume of 50μL to obtain a concentration of 0.25mg·mL. -1 The mixture was incubated in a Zr / Cu-UiO-66-NH2 suspension and 800 μL of buffer solution for 15 min. Then, 50 μL of 5 mM TMB solution and 50 μL of 15% H2O2 solution were added, and the mixture was incubated for another 20 min. The absorbance of the system was measured at a wavelength of 652 nm, and the colorimetric detection of fluoroquinolone antibiotics was performed based on the absorbance.

4. The application according to claim 2, characterized in that, The fluorescence detection method is as follows: Take 100 μL of Zr / Cu-UiO-66-NH2 suspension with a concentration of 2 mg / mL and place it in a container. Add 300 μL of a solution containing fluoroquinolone antibiotics. Add solvent to make the total volume of the mixed solution 4 mL. After mixing, collect the fluorescence emission spectrum and record the fluorescence intensity at 450 nm. The fluorescence detection of fluoroquinolone antibiotics is achieved based on the fluorescence intensity.

5. The application according to claim 1, characterized in that, The fluoroquinolone antibiotic in question is norfloxacin.

6. The application according to any one of claims 1-5, characterized in that, The preparation method of the Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme includes the following steps: zirconium chloride, copper nitrate trihydrate, and 2-aminoterephthalic acid are dissolved in DMF, and after ultrasonic treatment, glacial acetic acid is added, followed by ultrasonic treatment; the uniformly mixed solution is poured into a polytetrafluoroethylene autoclave, heated for reaction, and cooled to room temperature; the obtained product is collected by centrifugation, washed three times each with DMF and ethanol, and dried under vacuum at 60°C to obtain the product Zr / Cu-UiO-66-NH2 fluorescent-colorimetric bifunctional nanozyme.

7. The application according to claim 6, characterized in that, The molar ratio is zirconium chloride:copper nitrate trihydrate:2-aminoterephthalic acid = 0.4:0.6:

1.

8. The application according to claim 6, characterized in that, The duration of each ultrasonic treatment was 3 minutes.

9. The application according to claim 6, characterized in that, The heating reaction was carried out at 120°C for 24 hours.